Study on gamma radioactivity analysis from point sources using HPGe spectrometer by Full Spectrum Analysis method combined with Gold unfolding algorithm - Truong , Thi Hong Loan; Dang , Thi Thao My; Cao , Phuc Long Hoa (Nuclear Science and Technology, 2014)
In this work, the methodology of estimating the radioactivity of nuclides from point gamma source using method of full spectrum analysis combined with Gold unfolding algorithm are studied. The reference sources with known activities as Ba-133, Cd-109, Co-57, Co-60, Cs-137, Mn-54, Na-22 and Zn-65 are counted in front of the HPGe detector. The source which is mixed by these radioisotopes with known weighting factors C(i) are counted. Its spectra are unfolded to have the relative radioactivity of these isotopes from analyzed source, Cunf(i). The difference of less than 0.2% between calculated ratios of Cunf(i) from the unfolded spectra and known weighting factors of C(i) opens a possibility to improve the accuracy for the analysis method with low background HPGe detector.